Basic Principles of Decision Making upon Receipt of New Nanomaterial - Lyashenko, V.; Syed Khalid Mustafa; Sotnik, S.; M. Ayaz Ahmad (WARSE, 2019)
Review of nanomaterials existing classifications and their preparation methods is carried out. As a result, basic principles of decision-making when obtaining new nanomaterial are determined, which take into account stability, as well as properties when molding products from nanomaterials and directly reproducible properties of materials themselves with check for biocompatibility, biodegradability, and toxicity. It is proposed in decision-making process to pay attention to analysis: nanomaterial behavior in soil (mobility, stability); nanomaterials behavior in water; airborne behavior and photoactivity. It is proposed to classify nanomaterials in terms of their structural components: nanoparticles, carbon nanostructures, thin films. Proposed decision-making algorithm for obtaining new nanomaterial takes into account its safety for human health and environment throughout entire life cycle.
Keywords: Nanotechnology; Nanomaterial; Principles; Decision Making